Mental health and coping strategies in graduate students in the COVID-19 pandemic - Fabio Scorsolini-Comin; Naiana Dapieve Patias; Alisson Junior Cozzer; Pedro Augusto Warken Flores; Jean Von Hohendorff
Objective: to verify the relation of depression, anxiety, and stress symptoms with coping strategies in graduate students in the context of the new coronavirus pandemic (COVID-19). Method: an electronic cross-sectional and correlational survey was conducted with 331 Brazilian graduate students, aged 20-64 years old, who answered an online form containing a sociodemographic data questionnaire, a coping strategies scale, and the DASS-21 scale. Descriptive analysis, Mann-Whitney U or Kruskal-Wallis tests, and Spearman's correlation were performed. Results: the main results indicated that maintaining work and study routines, as well as a religious practice, is correlated with lower scores of depression, anxiety, and stress symptoms, as well as with coping strategies that can act as protective factors. Conclusion: the new coronavirus pandemic has strained public health and increased the need for studies aimed at understanding the impact of the event on the mental health of the population. It is suggested that employment and religiousness should be considered in interventions with graduate students.